Pengaruh Work Value Dan Disiplin Kerja Terhadap Kinerja Pegawai Dengan Gaya Kepemimpinan Sebagai Variabel Moderating - Riri Yamelda; Almasdi (Jurnal Ekonomi dan Bisnis Digital, 2022)
This study aims to determine and estimate: the influence of work values and work discipline on the performance of employees with leadership style as a moderating variable in the Agam Regency Regional Financial and Asset Management Agency. This type of research is associative descriptive quantitative. The population of this study were all employees of the Agam Regency Regional Finance and Asset Management Agency, totaling 52 employees. Sampling was carried out by means of a saturated sample of 52 people. Data was collected using a Likert scale model questionnaire. The data analysis technique is Smart PLS version 3. The results of the study are: (1) Work value has a positive and significant effect on employee performance. (2) Work discipline has a positive and significant effect on employee performance. (3) Leadership style has a positive and significant effect on employee performance. (4) Leadership style moderates work value t has a positive and insignificant effect on employee performance. (5) Leadership style moderates work discipline and has a positive and insignificant effect on employee performance